Criteria for Legal Competence in Islamic Law: A Critical Evaluation - Jamal, Irwansyah Muhammad; Mustaqim, Riza Afrian (Sharia and Law Faculty, 2023)
A leader must have the ability to act legally so that every action he does is legal. This skill is required to be perfect, even exceeding the ability to act legally on a husband and wife in managing a household or someone in managing their property. On the basis of perfect legal skills, the leadership process will be able to run well, and various benefits can be realized in society at large. In this case, Islamic law as one of the legal systems that live in society is believed in giving a view of the legal skills of a leader. Some verses of the Qur'an and the Hadith of the Prophet SAW. give a signal about the criteria for a leader's legal competence. There are two important elements that must be possessed so that the ability to act in law is perfect; first, the age of a leader (caliphate), either a leader of a state (prisident), or a region (governor and regent/mayor) is at least 40 years old. While the position of assistant to the caliphate (minister and police) must be at least 21 years old; second, having perfect intelligence (rusyd). This intelligence is based on deep knowledge and broad insight into leadership. Based on this intelligence, a leader will carry out policies to his people in accordance with the benefit principles. Seorang pemimpin menjadi sentral bagi rakyatnya untuk mengantarkan mereka dalam mewujudkan kemaslahatan, kesejahteraan, dan kehagiaaan. Untuk hal itu, seorang pemimpin diharuskan memiliki kecakapan hukum yang baik, bahkan melebihi daripada seorang suami atau isteri dalam membina rumah tangga, atau seseorang dalam mengelola harta bendanya. Konsep kecakapan hukum pada seorang pemimpin telah disebutkan dalam berbagai ketentuan atau pemikiran para ahli. Dalam hal ini, hukum Islam memberikan konsep dan kriteria kemampuan kecakapan bagi seorang pemimpin. Tulisan ini mengkaji konsep hukum Islam tentang kecakapan seorang pemimpin yang mampu mewujudkan kemaslahatan bagi umat. Metode yang digunakan pada kajian ini yuridis normatif, yakni dengan mengkaji beberapa ayat Alquran dan Hadis Nabi SAW. yang memberi isyarah tentang kriteria kecakapan hukum seorang pemimpin. Hasil penelitian ditemukan ada dua unsur penting yang harus dimiliki seorang pemimpin supaya cakap bertindak hukum secara sempurna. Pertama, usia seorang khalifah, baik Presiden, atau Gubernur dan Bupati/Walikota, minimal 40 tahun. Sementara jabatan pembantu khalifah, seperti Menteri dan Polisi minimal berumur 21 tahun. Kedua memiliki kecerdasan yang sempurna (rusyd), yakni seorang pemimpin mempunyai kecerdasan intelektual, emosional, dan spiritual yang baik. Dari ketiga kecerdasan tersebut akan melahirkan sifat bijaksana, dan pada gilirannya terwujud kemaslahatan hidup masyarakat secara luas.